Measuring Teachers’ Social-Emotional Competence: Development and Validation of a Situational Judgment Test - Aldrup, Karen; Carstensen, Bastian; Köller, Michaela M.; Klusmann, Uta (Frontiers in Psychology, 2020)
Teachers’ social-emotional competence is considered important to master the social and emotional challenges inherent in their profession and to build positive teacher-student relationships. In turn, this is key to both teachers’ occupational well-being and positive student development. Nonetheless, an instrument assessing the profession-specific knowledge and skills that teachers need to master the social and emotional demands in the classroom is still lacking. Therefore, we developed the Test of Regulation in and Understanding of Social Situations in Teaching (TRUST), which is a theory-based situational judgment test measuring teachers’ knowledge about strategies for emotion regulation and relationship management in emotionally and socially challenging situations with students. Results from three studies (N = 166 in-service teachers, N = 73 in-service teachers, N = 107 pre-service teachers) showed satisfactory internal consistency for both the emotion regulation and relationship management subtests. Furthermore, confirmatory factor analyses supported the differentiation between the two facets of social-emotional competence. Regarding convergent validity, results from Study 3 revealed a positive association between the profession-specific TRUST and pre-service teachers’ general emotional intelligence. Furthermore, small to moderate correlations with the Big Five personality traits provided evidence for the discriminant validity of TRUST. In Studies 1 and 2, we found evidence for a correlation with external criteria, that is, teachers with higher test scores reported providing more emotional support for students and having better teacher-student relationships. For teachers’ occupational well-being, we found a link with symptoms of depersonalization and job satisfaction, but none for emotional exhaustion. We will discuss the use of TRUST in research, for the evaluation of interventions, in teacher education, and professional development and will illustrate ideas for enhancing the tool.